1995
DOI: 10.3382/ps.0740666
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E in Viral Inactivated Vaccines

Abstract: This research aimed at verifying whether vitamin E added to inactivated and emulsified vaccines enhances the immune response to viral antigens in chicken. Three hundred and twenty broilers (males and females) and 16 types of vaccines, varying in viral antigen [Newcastle disease virus, egg drop syndrome 1976 virus (EDS76V), and infectious bursal disease virus] and vitamin E amount (replacing 10, 20, and 30% of mineral oil) were used. Results show that vaccines with vitamin E, especially when it replaces 20 or 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 8 publications
1
12
0
2
Order By: Relevance
“…Sahin et al (2001) reported that 250 mg/kg α-tocopherol acetate decreased serum AST and ALT in broilers reared under heat stress (32 °C). Franchini et al (1995) also noted that the AST level increased with vitamin E supplementation in young turkey; however, it decreased in old turkey (140 days old) which is quite consistent to our study. In this study, the reduction of serum AST and ALT seemed to be due to the antioxidant effect of vitamin E supplementation.…”
Section: Discussionsupporting
confidence: 92%
“…Sahin et al (2001) reported that 250 mg/kg α-tocopherol acetate decreased serum AST and ALT in broilers reared under heat stress (32 °C). Franchini et al (1995) also noted that the AST level increased with vitamin E supplementation in young turkey; however, it decreased in old turkey (140 days old) which is quite consistent to our study. In this study, the reduction of serum AST and ALT seemed to be due to the antioxidant effect of vitamin E supplementation.…”
Section: Discussionsupporting
confidence: 92%
“…This contact with the high local concentration of vitamin E (e.g. approximately 116 mg α-tocopherol per dose used) [23,24], at the site of action assures the most favourable immunoenhancing effect of the vitamin, far more effectively than is possible by its dietary administration [25].…”
Section: Immunoadjuvantmentioning
confidence: 99%
“…Also vitamin E has been successfully tested as an adjuvant in chicks showing, a significant improvement in antibody titers to Newcastle disease virus and E. coli antigens in the groups receiving the injection [23,24]. No data are available for pigs.…”
Section: Immunoadjuvantmentioning
confidence: 99%
“…Apart from its protective effect on lipid peroxidation, the immunoregulatory effects of dietary vitamin E on humoral and cell-mediated immunity are well known (Franchini et al, 1995;Raza et al, 1997;Shadaksharappa et al, 1997;Gu et al, 1999). Vitamin E improves the action of phagocytic cells, the responsiveness of antibodies to mitogens, and passive immune transfer (Tizzard, 1987).…”
Section: Introductionmentioning
confidence: 96%